A Case of Autosomal Recessive Woolly Hair/Hypotrichosis with Alternation in Severity: Deterioration and Improvement with Age - Naoko Matsuno; Makoto Kunisada; Haruhisa Kanki; Yutaka Simomura; Chikako Nishigori (Case Reports in Dermatology, 2013)
Autosomal recessive woolly hair/hypotrichosis (ARWH/H) is a nonsyndromic hair abnormality characterized by sparse, short and curly hair (WH/H). We report the case of a 3-year-old female, with no consanguineous ancestry, who exhibited WH/H. Normal hair was observed at birth, but severe hair loss had developed within the first 6 months; however, her hair density had improved somewhat by age 3. Light microscopy showed hair shaft invaginations, and polarized light microscopy suggested complete medullary disruption of the hair. Direct sequence analysis of peripheral blood showed a homozygous missense mutation in exon 6 of the lipase H gene (LIPH: c.736T>A, p.Cys246Ser), and the exact same mutation was found in the heterozygous state in both parents. The initial deterioration followed by improvement with age observed in this case suggests that the clinical course of ARWH/H may vary among patients with the same mutation in LIPH detected in this case, indicating that additional factors may influence the effect of LIPH on hair development.